Wetland soil microplastics are negatively related to vegetation cover and stem density - Helcoski, Ryan; Yonkos, Lance T.; Sanchez, Alterra; Baldwin, Andrew H. (Environmental pollution (1987), 2020)
Microplastics are a complex group of ubiquitous environmental contaminants of emerging concern. These particles degrade slowly, release plasticizers, and can be transferred between trophic levels. In aquatic systems, they have been identified suspended in the water column, along shorelines, and within sediment. However, the abundance and distribution of microplastics in vegetated wetlands, which are transitional ecosystems between terrestrial and aquatic environments, are poorly understood. Here we describe the spatial distribution of soil microplastics in habitats of varying vegetation density in an urban tidal wetland. Samples were wet-sieved, organic matter was oxidized using hydrogen peroxide, and microplastics separated under a dissecting microscope, counted, and weighed. A fraction (n = 175) were analyzed via FTIR for validation. Positive microplastics identification was 81%–93%. Dominant polymers were polystyrene (29%) and polyethylene and synthetic rubber (both 8%). Average microplastic number to a 5-cm depth (23,200 ± 2,500 m−2 or 1,270 ± 150 kg−1) varied between habitat types, where mudflat, channel edge, and drift line habitats all had significantly more total microplastics than the interior of dense stands of vegetation, suggesting that emergent wetland plants are a highly effective filter of microplastics. Microfibers were about eight times as abundant as microfragments, and fibers and fragments differed in their distribution patterns, with microfibers most abundant in vegetation-free mudflats and microfragments in vegetated channel edges. Our results demonstrate that vegetated wetlands are important locations for microplastic accumulation and that wetland vegetation and hydrodynamics affect spatial distribution of microplastics between habitats. [Display omitted] •Soil microplastics varied spatially in an urban wetland and averaged 23,200 m−2 (1,270 kg−1).•Microfiber concentration was negatively related to stem density and percent cover.•Microfibers were most abundant in mudflats and microfragments in channel edges.•Microfibers comprised 77–94% of total microplastics in an urban wetland. This study reveals that microplastics found throughout urban wetland soils are mostly microfibers and present at lower numbers in areas of dense vegetation compared to areas with few or no plants.